"Dual lock-and-key"-controlled ceria nanotubes-based nanozymes for tumor-specific photothermal therapy. (July 2021) - Chen, Ying; Yin, Chao; Zhang, Yutao; Liu, Yong; Zan, Jiahui; Xie, Chen; Fan, Quli; Huang, Wei
Abstract: Tumor-specific activatable therapy has gained more and more attention due to its improved therapeutic efficacy and minimized side effects. However, most of these nanomedicines only utilized one stimulus as the switch of the therapeutic process, which may have the issue of low selectivity. Herein, we develop a "dual lock-and-key" type activatable nanotherapeutic platform (ABTS@PAH-CNts) for tumor-specific photothermal therapy (PTT). Such nanoplatform can only be activated under both H2 O2 and acidic pH, thus achieving higher selectivity towards tumor than single stimulus-activated nanomedicine. The nanoplatform is prepared by adsorbing 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) onto the surface of ceria nanotubes. We demonstrate that ceria nanotubes have analogous peroxidase activity with natural horseradish peroxidase (HRP). Under both H2 O2 and acidic pH, ceria nanotubes can catalyze ABTS into its oxidized form, showing enhanced near-infrared (NIR) absorption with good photothermal effect. ABTS@PAH-CNts shows good in vitro biocompatibility without laser irradiation, while has good anticancer efficiency under 808 nm laser irradiation. In addition, in vivo study indicates that the photothermal temperature of ABTS@PAH-CNts can reach up to 55 °C in the tumor site, while only can reach 40 °C for normal tissue, demonstrating its good tumor specificity. Our work not only develops a nanozyme-based "dual lock-and-key"-controlled PTT system, but also provides a nanoplatform for activatable theranostics. Graphical abstract: Image 1 Highlights: The dual stimulus of H2 O2 and pH activate a nanozyme-based nanoplatform for tumor-specific photothermal therapy. Ceria nanotubes catalyze ABTS into oxidized form with enhanced near-infrared (NIR) absorption resulting in a good photothermal effect.